Enhancing Consumer Loyalty and Market Competitiveness: Approaching IPA-QFD in Product Development - Syaifuddin, Aldy Hamid; Ambarwati, Rita; Sari, Dewi Komala (BASKARA : Journal of Business and Entrepreneurship, 2024)
This paper provides an overview of AA.co.Store, is a fashion business founded in 2021. Despite being in the development stage, AA.co.Store can compete with other local brands in Sidoarjo. To maintain and attract more consumers, the company focuses on improving product quality. The success of a business is measured by the number of products produced and their competitiveness in the market. Product development is crucial to increase competitiveness and attract future consumers. The quality of the product and promotional activities significantly impact customer satisfaction. Pricing and distribution also influence purchasing decisions. To compete with competitors, AA.co.Store needs a comprehensive strategy. Research suggests that product quality, price, customer satisfaction, and brand image affect consumer loyalty and satisfaction. The purpose of this research is to improve AA.co.Store's product development using an IPA-QFD-based marketing mix aligned that very important for Development Goals (SDGs) of the store to compete with other local brands in Sidoarjo. The results of this study were AA.co.Store service quality, it can be concluded that Customer satisfaction with AA.co.Store services is fulfilled, which is indicated by the results of the questionnaire using the SERVQUAL method which does not show a negative value for the AA.co.Store brand when compared to other brands. There are three service quality attributes that need to be prioritised for improvement at AA.co.Store, namely the price of t-shirts that are more competitive than other brands, the condition of the parking lot, and cleanliness. There are several steps that can be taken to improve service quality based on technical needs, including: a.) changing the organisational strategy on company performance, especially in the operational section, b.) increasing the stock of materials to meet the number of orders, c.) providing training and development on existing SOPs, and d.) repairing and maintaining existing equipment in the company.